Ontogenetic instars of Lepidacarus maafushiensis sp. nov. from the Maldives, with remarks on morphological ontogeny of Lohmanniidae (Acari, Oribatida) - Bayartogtokh, Badamdorj; Ermilov, Sergey G.; Joharchi, Omid (Zootaxa, 2022)
Although the juvenile instars of oribatid mite family Lohmanniidae are well known compared to the other families of the infraorder Enarthronota, information on morphological ontogeny most known species is still lacking. Herein, a new species of the genus Lepidacarus is proposed from soil-litter of the Maafushi Island, Maldives, based on all ontogenetic instars. A comparative analysis of ontogenetic instars of species belonging various genera of Lohmanniidae is given, and the major characteristics of juvenile instars of 21 species are presented. From this analysis, it can be generalized that the juvenile morphologies of lohmanniid genera are quite similar and uniform, there is no significant features separating different genera of Lohmanniidae, and the juveniles of various genera differ from one another in the same characteristics as the adults.